Adhesive
A pressure-sensitive adhesive with a controlled acrylic copolymer addresses the challenges of cuttability, workability, and reliability in flexible devices by providing a storage modulus range that supports repeated deformation and recovery, ensuring high performance in thick film applications.
Patent Information
- Application Number
- JP2024531186
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-25
- Filing Date
- 2022-11-25
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing adhesives for flexible devices face challenges in maintaining cuttability, workability, reliability, and recovery properties, especially when subjected to repeated deformation, and achieving these properties in a thick adhesive form is difficult.
A pressure-sensitive adhesive using an acrylic copolymer with controlled monomer units to achieve a specific storage modulus range and crystallinity, allowing it to effectively follow deformation and recover, while maintaining excellent workability and reliability, even in thick film forms.
The adhesive exhibits a gentle storage modulus slope across temperatures, ensuring effective deformation and recovery, and maintains high workability, cuttability, and reliability, without defects like lifting, peeling, or bubble generation, suitable for flexible devices.
Smart Images

Figure 2024545861000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0164029 filed on November 25, 2021, and all contents disclosed in the documents of that patent application are incorporated herein by reference.
[0002] The present application relates to pressure sensitive adhesives. [Background technology]
[0003] A flexible device is a new concept of device, and examples of the flexible device include so-called foldable or rollable devices.
[0004] The adhesive applied to the flexible device is repeatedly folded and then unfolded, or wound and then unfolded, and therefore the adhesive applied to the flexible device is required to effectively follow the repeated deformation and to recover to its original shape when the force applied during deformation is removed.
[0005] It is generally known that the lower the elastic modulus of a pressure-sensitive adhesive, particularly the elastic modulus at low temperatures, the more effectively it can adapt to the repeated deformation.
[0006] However, if the elastic modulus of the adhesive layer is too low, the recovery property when the force applied for deformation is removed decreases, which leads to problems such as reduced cuttability and workability, making it difficult to ensure reliability when applied to a device.
[0007] Therefore, it is not easy to obtain a pressure-sensitive adhesive that effectively follows repeated deformation while satisfying requirements such as cuttability, workability, reliability, and recovery.
[0008] Depending on the design of a flexible device, the adhesive may be required to be thicker than conventional adhesives, i.e., a so-called thick-film adhesive. However, it is not an easy task to form a thick adhesive while still satisfying the physical properties required for the flexible device. Summary of the Invention [Problem to be solved by the invention]
[0009] The present application relates to an adhesive and its use. One object of the present application is to provide an adhesive suitable for a foldable device. In one example, one object of the present application is to provide an adhesive that ensures elastic properties suitable for a foldable device as well as cuttability, workability, recovery, and reliability.
[0010] Another object of the present application is to provide a pressure-sensitive adhesive that can satisfy the above physical properties even when the pressure-sensitive adhesive is formed relatively thick. [Means for solving the problem]
[0011] In the present specification, the physical properties are measured at room temperature unless otherwise specified, in cases where the measurement temperature affects the physical property.
[0012] The term "room temperature" as used herein means a temperature in a state in which the temperature is not particularly increased or decreased, and may mean any temperature within a range of about 10° C. to 30° C., for example, about 15° C. or higher, 18° C. or higher, 20° C. or higher, or about 23° C. or higher, and about 27° C. or lower. Unless otherwise specified, the unit of temperature referred to in this specification is ° C.
[0013] Of the physical properties referred to in this specification, the physical properties are those measured at normal pressure, unless otherwise specified in cases where the measurement pressure affects the physical properties.
[0014] In this specification, the term "normal pressure" refers to pressure in a state where there is no particular increase or decrease in pressure, and generally refers to a pressure of approximately 700 mmHg to 800 mmHg, which is the atmospheric pressure level.
[0015] In the present specification, unless otherwise specified, the physical properties are measured at the natural humidity at room temperature and pressure as described above, in cases where the humidity at which the properties are measured affects the physical properties.
[0016] The present application relates to an adhesive. The adhesive of the present application may include an adhesive polymer.
[0017] The adhesive polymer may be a polymer known in the art to be capable of forming an adhesive. The adhesiveness, as is well known, refers to the property of being able to adhere and peel by applying pressure at room temperature without using water, solvent, heat, etc.
[0018] In one example, the adhesive polymer may be an acrylic copolymer.
[0019] As used herein, the term copolymer means the result of the polymerization reaction of a mixture of monomers.
[0020] In this specification, the term "monomer unit" refers to the state of a monomer after the polymerization reaction.
[0021] The term "acrylic copolymer" as used herein refers to a copolymer containing an acrylic monomer unit as a main component. In this specification, the term "a component is contained as a main component" means that the content of the component is at a certain level or higher. For example, when the acrylic monomer unit is the main component in the acrylic copolymer, the lower limit of the ratio may be about 55% by weight, 60% by weight, 65% by weight, 70% by weight, 75% by weight, 80% by weight, 85% by weight, 90% by weight, or 95% by weight, and the upper limit may be about 100% by weight. The content may be equal to or greater than any of the lower limits, or may be equal to or greater than any of the lower limits but less than or equal to the upper limit.
[0022] As used herein, the term acrylic monomer means acrylic acid, methacrylic acid, an acrylic acid ester, or a methacrylic acid ester.
[0023] As used herein, the term (meth)acrylic means acrylic or methacrylic or a mixture thereof.
[0024] In the pressure-sensitive adhesive of the present application, when the adhesive polymer is crosslinkable, the polymer may be in a crosslinked state within the pressure-sensitive adhesive. Such a pressure-sensitive adhesive may be formed, for example, by crosslinking a pressure-sensitive adhesive composition containing the adhesive polymer.
[0025] The adhesive may contain the adhesive polymer as a main component. For example, the lower limit of the proportion of the adhesive polymer in the adhesive composition may be about 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 97 wt%, or 99 wt%, and the upper limit may be, for example, about 100 wt%. The content may be equal to or greater than any of the lower limits, or may be equal to or greater than any of the lower limits but less than or equal to the upper limit.
[0026] The pressure sensitive adhesive of the present application can exhibit a low storage modulus at low temperatures.
[0027] For example, the upper limit of the storage modulus of the pressure-sensitive adhesive at -20°C may be about 100,000 Pa, 98,000 Pa, 96,000 Pa, 94,000 Pa, 92,000 Pa, 90,000 Pa, 88,000 Pa, 86,000 Pa or 85,000 Pa, and the lower limit may be about 70,000 Pa, 72,000 Pa, 74,000 Pa, 76,000 Pa, 78,000 Pa, 80,000 Pa, 82,000 Pa, 84,000 Pa, 86,000 Pa, 88,000 Pa, 90,000 Pa, 92,000 Pa or 94,000 Pa. The storage modulus may be less than or equal to any of the upper limits described above, or may be greater than or equal to any of the lower limits described above but less than or equal to any of the upper limits described above. The storage modulus is a value measured by a temperature sweep method for measuring storage modulus described in the Examples of this specification.
[0028] The lower the storage modulus of the adhesive at low temperature, the better its ability to follow repeated deformation, but a storage modulus that is too low is disadvantageous in terms of the cuttability, workability, recovery, and reliability of the adhesive. Therefore, the storage modulus may be within a range that is equal to or exceeds any of the lower limits described above, and is equal to or exceeds any of the upper limits described above. When the adhesive exhibits a storage modulus within the above range at -20°C, it can be applied to flexible devices, effectively respond to repeated deformation and recovery, and can also appropriately ensure workability, cuttability, recovery, and reliability.
[0029] The pressure-sensitive adhesive of the present application exhibits a relatively low storage modulus at low temperatures as described above, and at the same time exhibits a storage modulus of a certain level or more at relatively high temperatures. The storage modulus of a pressure-sensitive adhesive is a function dependent on temperature, and generally, the storage modulus decreases as the temperature increases. Thus, the storage modulus of a pressure-sensitive adhesive at high temperatures is generally lower than its storage modulus at low temperatures. However, when a pressure-sensitive adhesive has a low storage modulus at low temperatures, the storage modulus at high temperatures also decreases relatively, and therefore, the storage modulus of a pressure-sensitive adhesive with a low storage modulus at low temperatures is lower than the storage modulus of a pressure-sensitive adhesive with a high storage modulus at low temperatures.
[0030] However, the pressure-sensitive adhesive of the present application can exhibit a relatively high storage modulus at high temperatures in addition to the low storage modulus at low temperatures, i.e., the pressure-sensitive adhesive of the present application can exhibit a relatively gentle slope in a graph of storage modulus versus temperature.
[0031] For example, the pressure-sensitive adhesive of the present application may have an absolute value of the rate of change ΔG1′ according to the following formula 1 within a predetermined range.
[0032] [Formula 1] △G1'=(G' 25 -G' -20 ) / 45
[0033] In formula 1, G' 25 is the storage modulus of the pressure sensitive adhesive at 25°C, and G' -20 is the storage modulus of the pressure-sensitive adhesive at −20° C. The storage modulus is a value measured by the storage modulus measurement method (temperature sweep) described in the Examples of this specification.
[0034] The upper limit of the rate of change ΔG1′ may be about 1,700, 1,650, 1,600, 1,550, 1,500, 1,450, 1,400, or 1,370, and the lower limit may be about 800, 900, 1,000, 1,100, 1,200, 1,300, 1,400, 1,500, or 1,600. ΔG1′ may be less than or less than any of the upper limits described above, or may be greater than or exceeding any of the lower limits described above while being less than or equal to any of the upper limits described above.
[0035] An adhesive exhibiting such a rate of change can effectively follow the repeated deformation and recovery in a foldable device, and can maintain excellent workability, cuttability, recovery, and reliability. As described above, an adhesive having a low modulus of elasticity at low temperatures exhibits a relatively low modulus of elasticity at high temperatures, so it is not an easy task to satisfy the rate of change. In the present application, the rate of change can be satisfied by applying a specific acrylic copolymer described below as the adhesive polymer.
[0036] ΔG1′ in formula 1 may be a negative number.
[0037] The storage modulus of the pressure-sensitive adhesive at 25° C. may also be within a predetermined range. The storage modulus is a value measured by the storage modulus measurement method (temperature sweep) described in the Examples of this specification. For example, the lower limit of the storage modulus at 25°C may be about 10,000 Pa, 12,000 Pa, 14,000 Pa, 16,000 Pa, 18,000 Pa, 20,000 Pa, 22,000 Pa, 24,000 Pa, 26,000 Pa, 28,000 or 30,000 Pa, and the upper limit may be about 100,000 Pa, 98,000 Pa, 96,000 Pa, 94,000 Pa, 92,000 Pa, 90,000 Pa, 88,000 Pa, 86,000 Pa, 84,000 Pa, 82,000 Pa, 80,000 Pa, 78,000 Pa, 76,0 The pressure may be approximately 00 Pa, 74,000 Pa, 72,000 Pa, 70,000 Pa, 68,000 Pa, 66,000 Pa, 64,000 Pa, 62,000 Pa, 60,000 Pa, 58,000 Pa, 56,000 Pa, 54,000 Pa, 52,000 Pa, 50,000 Pa, 48,000 Pa, 46,000 Pa, 44,000 Pa, 42,000 Pa, 40,000 Pa, 38,000 Pa, 36,000 Pa, 34,000 Pa, 32,000 Pa, 30,000 Pa, 28,000 Pa, 26,000 Pa or 24,000 Pa. The storage modulus may be equal to or greater than any of the lower limits mentioned above, or may be equal to or greater than any of the lower limits mentioned above but less than or equal to any of the upper limits mentioned above.
[0038] The pressure-sensitive adhesive may have an absolute value of a rate of change ΔG2′ according to the following formula 2 within a predetermined range.
[0039] [Formula 2] △G2'=(G' 60 -G' -20 ) / 80
[0040] In formula 1, G' 60 is the storage modulus of the pressure sensitive adhesive at 60° C., and G' -20is the storage modulus of the pressure-sensitive adhesive at −20° C. The storage modulus is a value measured by the storage modulus measurement method (temperature sweep) described in the Examples of this specification.
[0041] The upper limit of the rate of change ΔG2′ may be about 2,000, 1,500, 1,000, 950, 900 or 870, and the lower limit may be about 400, 500, 600, 700, 800, 850, 900 or 950. The rate of change ΔG2′ may be equal to or greater than any one of the upper limits, or may be equal to or greater than any one of the lower limits but less than or equal to any one of the upper limits.
[0042] An adhesive exhibiting such a rate of change can effectively follow the repeated deformation and recovery in a foldable device, and can also maintain excellent workability, cuttability, recovery, and reliability.
[0043] ΔG2′ in Equation 2 may be a negative number.
[0044] The pressure-sensitive adhesive may have a storage modulus within a predetermined range at 60° C. The storage modulus is a value measured by a temperature sweep method for measuring storage modulus described in the Examples of this specification. The lower limit of the storage modulus at 60°C may be about 5,000 Pa, 10,000 Pa, 12,000 Pa, 14,000 Pa, 16,000 Pa, 18,000 Pa, 20,000 Pa, or 22,000 Pa, and the upper limit may be about 100,000 Pa, 98,000 Pa, 96,000 Pa, 94,000 Pa, 92,000 Pa, 90,000 Pa, 88,000 Pa, 86,000 Pa, 84,000 Pa, 82,000 Pa, 80,000 Pa, 78,000 Pa, 76,000 Pa, 74,000 Pa, 72,000 Pa, 70,000 Pa, 68 ,000 Pa, 66,000 Pa, 64,000 Pa, 62,000 Pa, 60,000 Pa, 58,000 Pa, 56,000 Pa, 54,000 Pa, 52,000 Pa, 50,000 Pa, 48,000 Pa, 46,000 Pa, 44,000 Pa, 42,000 Pa, 40,000 Pa, 38,000 Pa, 36,000 Pa, 34,000 Pa, 32,000 Pa, 30,000 Pa, 28,000 Pa, 26,000 Pa, 24,000 Pa, 22,000 Pa, 20,000 Pa, 18,000 Pa or 16,000 Pa. The storage modulus may be equal to or greater than any of the lower limits mentioned above, or may be equal to or greater than any of the lower limits mentioned above but less than or equal to any of the upper limits mentioned above.
[0045] In the pressure-sensitive adhesive of the present application, the absolute value of the rate of change ΔG3′ according to the following formula 3 may be within a predetermined range.
[0046] [Formula 3] △G3'=(G' 60 -G' 25 ) / 35
[0047] In formula 3, G' 60 is the storage modulus of the pressure sensitive adhesive at 60° C., and G' 25is the storage modulus of the pressure-sensitive adhesive at 25° C. The storage modulus is a value measured by the storage modulus measurement method (temperature sweep) described in the Examples of this specification.
[0048] The upper limit of the rate of change ΔG3′ may be about 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, 300, or 250, and the lower limit may be about 50, 100, 150, or 200. ΔG3′ may be less than or below any of the above upper limits, or may be greater than or exceed any of the above lower limits but within a range of less than or below any of the above upper limits.
[0049] An adhesive exhibiting such a rate of change can effectively follow the repeated deformation and recovery in a foldable device, and can also maintain excellent workability, cuttability, recovery, and reliability.
[0050] ΔG3′ in Equation 3 may be a negative number.
[0051] When an adhesive is designed to have the above-mentioned properties, it is possible to provide an adhesive that has excellent workability, cuttability, recovery and reliability while ensuring the desired properties, i.e., the properties required for flexible devices.
[0052] In particular, by satisfying the above physical properties, even if the adhesive is formed relatively thick, it is possible to provide an adhesive that has excellent characteristics, workability, cuttability, recovery, and reliability required for the flexible device.
[0053] For example, the adhesive may be formed so that TM according to the following formula 4 falls within a predetermined range.
[0054] [Formula 4] TM=D / G' -20
[0055] In formula 4, D is the thickness of the adhesive (unit: 400 μm), and G′ -20 is the storage modulus of the pressure-sensitive adhesive at -20°C (unit: MPa).
[0056] For example, the pressure sensitive adhesive has a lower limit of TM according to formula 4 of 400 μm MPa -1 , 450μm·MPa -1 , 500μm·MPa -1 , 550μm·MPa -1 , 600μm·MPa -1 , 650μm·MPa -1 , 700μm·MPa -1 , 750μm·MPa -1 , 800μm·MPa -1 , 850μm·MPa -1 , 900μm·MPa -1 , 950μm·MPa -1 , 1,000μm·MPa -1 or 1,050μm·MPa -1 The upper limit is 2,000 μm·MPa. -1 , 1,800μm·MPa -1 , 1,600μm·MPa -1 , 1,400μm·MPa -1 , 1,200μm·MPa -1 or 1,100μm·MPa -1 The TM may be equal to or greater than any of the lower limits mentioned above, or may be equal to or greater than any of the lower limits mentioned above but less than or equal to any of the upper limits mentioned above.
[0057] In the present application, in order to form the above-mentioned adhesive, a specific acrylic copolymer is applied as the adhesive polymer.
[0058] For example, the acrylic copolymer may be an acrylic copolymer exhibiting crystallinity. In the present application, the acrylic copolymer exhibiting crystallinity means that the melting point (Tm, melting point) is confirmed by the DSC (Differential Scanning Calorimeter) measurement method described in the examples of the present specification. In the present specification, the melting point and the melting temperature have the same meaning.
[0059] Acrylic copolymers are generally non-crystalline copolymers, and in the present application, crystallinity is imparted to the copolymer through control of the monomer units of the acrylic copolymer.
[0060] In particular, in the present application, a copolymer having both a glass transition temperature (Tg) and a melting point may be used as the acrylic copolymer, thereby effectively forming a desired adhesive. In the above, having both a glass transition temperature and a melting point means that the glass transition temperature and the melting point are confirmed simultaneously in the DSC (Differential Scanning Calorimeter) measurement method.
[0061] The melting point and glass transition temperature may be adjusted to ensure desired properties.
[0062] For example, the upper limit of the glass transition temperature of the acrylic copolymer may be about −30° C., −35° C., −40° C., −45° C., −50° C., −55° C., or −60° C., and the lower limit may be about −10° C., −15° C., −20° C., −25° C., −30° C., −35° C., −40° C., −45° C., −50° C., −55° C., or −60° C. The glass transition temperature may be equal to or greater than any of the lower limits described above, or equal to or less than any of the upper limits described above, or equal to or greater than any of the lower limits described above but less than or less than any of the upper limits described above.
[0063] The lower limit of the melting point of the acrylic copolymer may be about -10° C., -15° C., -20° C., -25° C., -30° C., -35° C. or -40° C., and the upper limit may be about -5° C., -10° C., -15° C., -20° C., -25° C., -30° C., -35° C. or -40° C. The melting point may be equal to or greater than any of the lower limits mentioned above, or equal to or less than any of the upper limits mentioned above, or equal to or greater than any of the lower limits mentioned above but less than or less than any of the upper limits mentioned above.
[0064] The difference between the melting point (Tm) and the glass transition temperature (Tg) of the acrylic copolymer may be within a predetermined range. The difference is the melting point (Tm) minus the glass transition temperature (Tg) (Tm-Tg). The lower limit of the difference (Tm-Tg) may be, for example, about 5°C, 7°C, 9°C, 10°C, 11°C, 13°C, 15°C, 17°C, 19°C, 20°C, 22°C, 25°C, 27°C, 30°C, 32°C, 35°C, 37°C, or 40°C, and the upper limit may be about 100°C, 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, 60°C, 55°C, 50°C, 45°C, 40°C, 35°C, 30°C, 25°C, or 20°C. The difference (Tm-Tg) may be equal to or greater than any of the lower limits mentioned above, or equal to or less than any of the upper limits mentioned above, or may be equal to or greater than any of the lower limits but less than or less than any of the upper limits mentioned above.
[0065] By using an acrylic copolymer exhibiting such properties, desired properties can be efficiently secured.
[0066] The acrylic copolymer may contain at least an alkyl (meth)acrylate unit, a unit of the following formula 1, and a polar functional group-containing unit.
[0067] Moreover, the term "unit" means a monomer unit.
[0068] [ka]
[0069] In Chemical formula 1, R1 represents a hydrogen atom or an alkyl group, and R2 represents an alkyl group having 11 to 13 carbon atoms.
[0070] Acrylic copolymers containing the above monomer units are effective in forming the desired adhesive.
[0071] The acrylic copolymer may be formed from the above-mentioned crystalline copolymer with a predetermined ratio of the unit of Chemical Formula 1 and / or the polar functional group-containing unit, or may be formed from a copolymer having similar properties.
[0072] For example, when the units of Chemical formula 1 are present in a predetermined ratio, and when the units of Chemical formula 1 interact with polar functional groups present in a predetermined ratio, such a copolymer may exhibit crystallinity or at least a property similar to crystallinity. When a copolymer having crystallinity or a property similar to crystallinity is applied, a pressure-sensitive adhesive having the above-mentioned properties can be effectively formed. Therefore, a pressure-sensitive adhesive having the above-mentioned elastic modulus properties can be effectively formed through a pressure-sensitive adhesive to which such a copolymer is applied.
[0073] As the alkyl(meth)acrylate unit contained in the copolymer, for example, a unit derived from an alkyl(meth)acrylate having an alkyl group having 1 to 10 carbon atoms may be used. In other examples, the alkyl group may be an alkyl group having 2 to 20 carbon atoms, 3 to 10 carbon atoms, 4 to 10 carbon atoms, 4 to 10 carbon atoms, 4 to 9 carbon atoms, or 4 to 8 carbon atoms. The alkyl group may be linear or branched, and may be substituted or unsubstituted. In one example, the unit may be formed using an alkyl(meth)acrylate having a linear or branched, unsubstituted alkyl group as the alkyl group.
[0074] Examples of the alkyl (meth)acrylate include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, sec-butyl (meth)acrylate, pentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, isononyl (meth)acrylate, n-octyl (meth)acrylate, and isooctyl (meth)acrylate.
[0075] The lower limit of the proportion of the alkyl (meth)acrylate unit in the acrylic copolymer may be about 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, or 40 wt%, and the upper limit may be about 70 wt%, 65 wt%, 60 wt%, 55 wt%, 50 wt%, 45 wt%, 40 wt%, 35 wt%, 30 wt%, 25 wt%, or 20 wt%. The proportion may be equal to or greater than any of the lower limits, or equal to or less than any of the upper limits, or equal to or greater than any of the lower limits but equal to or less than any of the upper limits. A desired adhesive may be effectively formed within such a range.
[0076] The polar functional group-containing unit is a unit formed by a monomer having a polar functional group. Such a monomer usually contains both a polymerizable group (e.g., a carbon-carbon double bond) and a polar functional group.
[0077] Examples of the monomer having a polar functional group include a hydroxyl group-containing monomer, a carboxyl group-containing monomer, and a nitrogen-containing monomer. In the present application, it is particularly advantageous to apply a hydroxyl group-containing monomer, but the present invention is not limited thereto.
[0078] Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 2-hydroxypolyethylene glycol (meth)acrylate, or 2-hydroxypolypropylene glycol (meth)acrylate, and examples of carboxyl group-containing monomers include (meth)acrylic acid, 2-(meth)acryloyloxyacetic acid, 3-(meth)acryloyloxypropyl acid, 4-(meth)acryloyloxybutyric acid, acrylic acid dimer, itaconic acid, maleic acid, and maleic anhydride, and examples of nitrogen-containing monomers include, but are not limited to, (meth)acrylamide, N-vinylpyrrolidone, or N-vinylcaprolactam. One or more of the above may be used in combination.
[0079] In one example, the polar functional group-containing unit may be a hydroxy-containing monomer unit, specifically a hydroxyalkyl(meth)acrylate unit, in which the carbon number of the alkyl in the hydroxyalkyl moiety is 1 to 20, 1 to 16, 1 to 12, 1 to 8, 1 to 4, or 2 to 4. The alkyl in the hydroxyalkyl moiety may be linear or branched.
[0080] The lower limit of the ratio of the polar functional group-containing units to 100 parts by weight of the alkyl (meth)acrylate units may be about 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, or 100 parts by weight, and the upper limit of the ratio may be about 200 parts by weight, 195 parts by weight, 19 parts by weight, 200 parts by weight, 200 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, or 100 parts by weight. The ratio may be about 0 parts by weight, 185 parts by weight, 180 parts by weight, 175 parts by weight, 170 parts by weight, 165 parts by weight, 160 parts by weight, 155 parts by weight, 150 parts by weight, 145 parts by weight, 140 parts by weight, 135 parts by weight, 130 parts by weight, 125 parts by weight, 120 parts by weight, 115 parts by weight, 110 parts by weight, 105 parts by weight, 100 parts by weight, 95 parts by weight, 90 parts by weight, 85 parts by weight, 80 parts by weight, 75 parts by weight, 70 parts by weight, 65 parts by weight, 60 parts by weight, or 55 parts by weight. The ratio may be equal to or greater than any of the lower limits described above, or equal to or greater than any of the lower limits described above, but equal to or less than any of the upper limits described above.
[0081] The unit of Chemical Formula 1 is a unit containing a long-chain alkyl group, and when such a unit is contained in a copolymer in a certain proportion or more, it can interact with a polar functional group depending on the case and impart crystallinity or crystal-like properties to the copolymer.
[0082] In the unit of Chemical Formula 1, R1 may be hydrogen or an alkyl group having 1 to 4 carbon atoms, specifically, hydrogen, a methyl group, or an ethyl group.
[0083] In Chemical formula 1, R2 is an alkyl group having 11 to 13 carbon atoms, and such an alkyl group may be linear or branched, and may be substituted or unsubstituted. In one example, R2 may be a linear, unsubstituted alkyl group. For example, lauryl (meth)acrylate and / or tetradecyl (meth)acrylate may be used to form the unit of Chemical formula 1.
[0084] The lower limit of the weight ratio of the unit of Chemical Formula 1 to 100 parts by weight of the alkyl (meth)acrylate unit is 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, 100 parts by weight, 105 parts by weight, 110 parts by weight, 115 parts by weight, 120 parts by weight, 125 parts by weight, 130 parts by weight, 135 parts by weight, 140 parts by weight, 145 parts by weight, 150 parts by weight, 155 parts by weight, 160 parts by weight, 175 parts by weight, 180 parts by weight, 185 parts by weight, 190 parts by weight, 195 parts by weight, 200 parts by weight, 205 parts by weight, 210 parts by weight, 215 parts by weight, 220 parts by weight, 225 parts by weight, 230 parts by weight, 235 parts by weight, 240 parts by weight, 245 parts by weight, 250 parts by weight, 260 parts by weight, 270 parts by weight, 280 parts by weight, 290 parts by weight, 300 parts by weight, 310 parts by weight, 320 parts by weight, 330 parts by weight, 340 parts by weight, 350 parts by weight, 360 parts by weight, 370 parts by weight, 380 parts by weight, 390 parts by weight, 400 parts by weight, 410 parts by weight, 420 parts by weight, 430 parts by weight, 440 parts by weight, 450 parts by weight, 460 parts by weight, 470 parts by weight, 480 parts by weight, 490 parts by weight, 500 parts by weight, 510 parts by weight, 520 parts by weight, 53 It may be about 40 parts by weight, 245 parts by weight, 250 parts by weight, 255 parts by weight, 260 parts by weight, 275 parts by weight, 280 parts by weight, 285 parts by weight, 290 parts by weight, 295 parts by weight, or 300 parts by weight, and the upper limit is 600 parts by weight, 595 parts by weight, 590 parts by weight, 585 parts by weight, 580 parts by weight, 575 parts by weight, 570 parts by weight, 565 parts by weight, 560 parts by weight, 555 parts by weight, 550 parts by weight, 545 parts by weight, 540 parts by weight, 535 parts by weight, 530 parts by weight, 525 parts by weight, 520 parts by weight, 515 parts by weight, 510 parts by weight, 505 parts by weight, 500 parts by weight, 495 parts by weight, 490 parts by weight, and the upper limit is about ... Parts by weight, 485 parts by weight, 480 parts by weight, 475 parts by weight, 470 parts by weight, 465 parts by weight, 460 parts by weight, 455 parts by weight, 450 parts by weight, 445 parts by weight, 440 parts by weight, 435 parts by weight, 430 parts by weight, 425 parts by weight, 420 parts by weight, 415 parts by weight, 410 parts by weight, 405 parts by weight, 400 parts by weight Parts by weight, 395 parts by weight, 390 parts by weight, 385 parts by weight, 380 parts by weight, 375 parts by weight, 370 parts by weight, 365 parts by weight, 360 parts by weight, 355 parts by weight, 350 parts by weight, 345 parts by weight, 340 parts by weight, 335 parts by weight, 330 parts by weight, 325 parts by weight, 320 parts by weight, 315 parts by weight, 31 0 parts by weight, 305 parts by weight, 300 parts by weight, 295 parts by weight, 290 parts by weight, 285 parts by weight, 280 parts by weight, 275 parts by weight, 270 parts by weight, 265 parts by weight, 260 parts by weight, 255 parts by weight, 250 parts by weight, 245 parts by weight, 240 parts by weight, 235 parts by weight, 230 parts by weight, 225 parts by weight, 2 20 parts by weight, 215 parts by weight, 210 parts by weight, 205 parts by weight, 200 parts by weight, 195 parts by weight, 190 parts by weight, 185 parts by weight, 180 parts by weight, 175 parts by weight, 170 parts by weight, 165 parts by weight, 160 parts by weight, 155 parts by weight, 150 parts by weight, 145 parts by weight, 140 parts by weight, 135 parts by weight,The ratio may be about 130 parts by weight, 125 parts by weight, 120 parts by weight, 115 parts by weight, 110 parts by weight, 105 parts by weight, or 100 parts by weight. The ratio may be equal to or greater than any of the lower limits mentioned above, or equal to or less than any of the upper limits mentioned above, or equal to or greater than any of the lower limits mentioned above but less than or less than any of the upper limits mentioned above.
[0085] The ratio of the monomer units may be adjusted so that the acrylic copolymer simultaneously exhibits the above-mentioned glass transition temperature and melting point.
[0086] That is, the acrylic copolymer containing the above-mentioned three types of monomer units in a certain ratio is likely to have crystallinity or exhibit properties similar to crystallinity, but the composition of the acrylic copolymer may be further adjusted so that it simultaneously has the above-mentioned melting point and glass transition temperature.
[0087] For example, in order for the acrylic copolymer to exhibit the above-mentioned crystallinity, the units of Chemical formula 1 must be contained in an amount of at least 90 parts by weight relative to 100 parts by weight of the alkyl (meth)acrylate units. In another example, the ratio of the units of Chemical formula 1 in the crystalline acrylic copolymer is 95 parts by weight or more, 100 parts by weight or more, 105 parts by weight or more, 110 parts by weight or more, 115 parts by weight or more, 120 parts by weight or more, 125 parts by weight or more, 130 parts by weight or more, 135 parts by weight or more, 140 parts by weight or more, 145 parts by weight or more, 150 parts by weight or more, 155 parts by weight or more, 160 parts by weight or more, 175 parts by weight or more, 180 parts by weight or more, 185 parts by weight or more, 190 parts by weight or more, 1 about 95 parts by weight or more, 200 parts by weight or more, 205 parts by weight or more, 210 parts by weight or more, 215 parts by weight or more, 220 parts by weight or more, 225 parts by weight or more, 230 parts by weight or more, 235 parts by weight or more, 240 parts by weight or more, 245 parts by weight or more, 250 parts by weight or more, 255 parts by weight or more, 260 parts by weight or more, 275 parts by weight or more, 280 parts by weight or more, 285 parts by weight or more, 290 parts by weight or more, 295 parts by weight or more, or 300 parts by weight or more, or about 500 parts by weight or less, 495 parts by weight or less, 490 parts by weight or less, 485 parts by weight or less , 480 parts by weight or less, 475 parts by weight or less, 470 parts by weight or less, 465 parts by weight or less, 460 parts by weight or less, 455 parts by weight or less, 450 parts by weight or less, 445 parts by weight or less, 440 parts by weight or less, 435 parts by weight or less, 430 parts by weight or less, 425 parts by weight or less, 420 Parts by weight or less, 415 parts by weight or less, 410 parts by weight or less, 405 parts by weight or less, 400 parts by weight or less, 395 parts by weight or less, 390 parts by weight or less, 385 parts by weight or less, 380 parts by weight or less, 375 parts by weight or less, 370 parts by weight or less, 365 parts by weight or less, 360 parts by weight or less , 355 parts by weight or less, 350 parts by weight or less, 345 parts by weight or less, 340 parts by weight or less, 335 parts by weight or less, 330 parts by weight or less, 325 parts by weight or less, 320 parts by weight or less, 315 parts by weight or less, 310 parts by weight or less, 305 parts by weight or less, 300 parts by weight or less, 295 parts by weight or less parts by weight or less, 290 parts by weight or less, 285 parts by weight or less, 280 parts by weight or less, 275 parts by weight or less, 270 parts by weight or less, 265 parts by weight or less, 260 parts by weight or less, 255 parts by weight or less, 250 parts by weight or less, 245 parts by weight or less, 240 parts by weight or less, 235 parts by weight or less,It may be about 230 parts by weight or less, 225 parts by weight or less, 220 parts by weight or less, 215 parts by weight or less, 210 parts by weight or less, 205 parts by weight or less, 200 parts by weight or less, 195 parts by weight or less, 190 parts by weight or less, 185 parts by weight or less, 180 parts by weight or less, 175 parts by weight or less, 170 parts by weight or less, 165 parts by weight or less, 160 parts by weight or less, 155 parts by weight or less, 150 parts by weight or less, 145 parts by weight or less, 140 parts by weight or less, 135 parts by weight or less, 130 parts by weight or less, 125 parts by weight or less, 120 parts by weight or less, 115 parts by weight or less, 110 parts by weight or less, 105 parts by weight or less, or 100 parts by weight or less.
[0088] In the crystalline acrylic copolymer, the ratio (A / B) of the weight (A) of the unit of the formula 1 to the weight (B) of the polar functional group-containing unit may be controlled. For example, the lower limit of the ratio (A / B) may be about 1, 1.2, 1.4, 1.5, 1.7, 1.9, 2.1, 2.3, 2.5, 2.7 or 2.9, and the upper limit may be about 10, 9, 8, 7, 6, 5, 4, 3, 2.5 or 2. The ratio may be equal to or greater than any of the lower limits described above, or equal to or less than any of the upper limits described above, or equal to or greater than any of the lower limits described above but equal to or less than any of the upper limits described above. In the crystalline acrylic copolymer, the polar functional group-containing unit may be a hydroxyl group-containing unit. In one example, a hydroxyalkyl (meth)acrylate having a hydroxyalkyl group with 3 to 6 carbon atoms, 3 to 5 carbon atoms, 3 to 4 carbon atoms, or about 4 carbon atoms can appropriately form the crystalline acrylic copolymer. Although the reason is not clear, it is considered that the interaction between the alkyl group (R2) of the unit of Chemical Formula 1 and the hydroxyalkyl group contributes to the development of crystallinity of the acrylic copolymer.
[0089] The crystalline acrylic copolymer may contain the alkyl (meth)acrylate unit in a ratio within the range of about 15 to 55% by weight. In other examples, the ratio of the alkyl (meth)acrylate unit may be 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, or 40% by weight or more, and may be about 50% by weight or less, 45% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, or 20% by weight or less. Within such a range, a desired pressure-sensitive adhesive layer can be effectively formed.
[0090] It is believed that the interaction or regularity of the monomer units contained in the above ratio imparts crystallinity to the acrylic copolymer, and the melting point is confirmed.
[0091] The acrylic copolymer may contain other monomer units in addition to the above-mentioned monomer units as appropriate, so long as the purpose is not impaired (for example, the crystallinity of the copolymer is not impaired).
[0092] For example, the acrylic copolymer (adhesive polymer) may further contain a monomer unit of the following formula 2. The monomer unit of the following formula 2 is an optional monomer unit and may not be contained in the acrylic copolymer.
[0093] [ka]
[0094] In Chemical Formula 2, R1 represents hydrogen or an alkyl group, and R3 represents an aromatic ketone group or a (meth)acryloyl group.
[0095] The unit of Chemical Formula 2 is a unit containing an aromatic ketone group or a (meth)acryloyl group in the side chain.
[0096] In the pressure-sensitive adhesive, the aromatic ketone group or (meth)acryloyl group may exist as is, or may exist after undergoing a hydrogen elimination reaction or a radical reaction, which will be described later.
[0097] In the unit of formula 2, the aromatic ketone group refers to an aromatic ketone group or a substituent containing such an aromatic ketone group that induces hydrogen abstraction from a polymer chain when exposed to electromagnetic waves.
[0098] When exposed to electromagnetic waves, the aromatic ketone groups can remove hydrogen atoms from other polymer chains or from other portions of the polymer chain. Such removal can lead to the formation of radicals that can form cross-links between polymer chains or within the same polymer chain. Categories of such aromatic ketone groups include, for example, aromatic ketone groups such as derivatives of benzophenone, acetophenone, or anthroquinone.
[0099] Examples of monomers that derive the unit of formula 2 having an aromatic ketone group include, but are not limited to, 4-benzoylphenyl (meth)acrylate, 4-(meth)acryloyloxyethoxybenzophenone, 4-(meth)acryloyloxy-4'-methoxybenzophenone, 4-(meth)acryloyloxyethoxy-4'-methoxybenzophenone, 4-(meth)acryloyloxy-4'-bromobenzophenone, and / or 4-acryloyloxyethoxy-4'-bromobenzophenone.
[0100] In the unit of Chemical Formula 2, the (meth)acryloyl group means a (meth)acryloyl group or a substituent containing the same that induces free radical polymerization when exposed to electromagnetic waves in the presence of a suitable radical initiator. Such a (meth)acryloyl group can act similarly to the aromatic ketone group when exposed to electromagnetic waves.
[0101] The unit of formula 2 in which R3 is a (meth)acryloyl group may be formed, for example, by preparing a precursor copolymer and then further reacting with an unsaturated reagent compound to introduce a (meth)acryloyl group. Typically, the introduction of the (meth)acryloyl group involves (1) a reaction between a nucleophilic group on the precursor copolymer and an electrophilic group on the unsaturated reagent compound (i.e., the unsaturated reagent compound contains both an electrophilic group and a (meth)acryloyl group), or (2) a reaction between an electrophilic group on the precursor copolymer and a nucleophilic group on the unsaturated reagent compound (i.e., the unsaturated reagent compound contains both a nucleophilic group and a (meth)acryloyl group). These reactions between nucleophilic groups and electrophilic groups are typically ring-opening reactions, addition reactions, or condensation reactions.
[0102] In this case, the precursor copolymer has hydroxy, carboxylic acid (-COOH), or anhydride (-O-(CO)-O-) groups. If the precursor copolymer has hydroxy groups, the unsaturated reagent compound has carboxylic acid (-COOH), isocyanate (-NCO), epoxy (i.e., oxiranyl), or anhydride groups in addition to the (meth)acryloyl groups. If the precursor copolymer has carboxyl groups, the unsaturated reagent compound has hydroxy, amino, epoxy, isocyanate, aziridinyl, azetidinyl, or oxazolinyl groups in addition to the (meth)acryloyl groups. If the precursor (meth)acrylate copolymer has anhydride groups, the unsaturated reagent compound has hydroxy or amine groups in addition to the (meth)acryloyl groups.
[0103] In one example, the precursor copolymer has a carboxyl group and the unsaturated reagent compound may have an epoxy group. Exemplary unsaturated reagent compounds include, for example, glycidyl (meth)acrylate and 4-hydroxybutyl acrylate glycidyl ether. In another example, the precursor copolymer has an anhydride group that reacts with an unsaturated reagent compound such as a hydroxy-substituted alkyl (meth)acrylate, for example, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, etc. In yet another example, the precursor copolymer has a hydroxy group and the unsaturated reagent compound has an isocyanate group and a (meth)acryloyl group. Such unsaturated reagent compounds include, but are not limited to, isocyanato alkyl (meth)acrylate, for example, isocyanato ethyl (meth)acrylate.
[0104] In one example, the (meth)acryloyl group has the formula CH2=CHR 1 It is represented by -(CO)-QL-, where L is a linking group and Q is oxy (-O-) or -NH-. The L includes alkylene, arylene, or a combination thereof, and further includes -O-, -O-(CO)-, -NH-(CO)-, -NH-, or a combination thereof depending on the precursor copolymer and the specific unsaturated reagent compound reacting to form a (meth)acryloyl group. In some specific examples, the (meth)acryloyl group is represented by the chemical formula -(CO)-OR of the precursor copolymer. 5 Hydroxy-containing groups represented by -OH and the chemical formula H2C=CHR 1 -(CO)-OR 6 -H2C=CHR formed by reaction with an unsaturated reagent compound which is an isocyanato alkyl (meth)acrylate represented by -NCO 1- (CO)-OR 6 -NH-(CO)-OR 5 -O-(CO)-. 5 and R 6are each independently an alkylene group, for example, an alkylene group having 1 to 10 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms. 1 is methyl or hydrogen.
[0105] In the unit of Chemical Formula 2, R1 may be hydrogen or an alkyl group having 1 to 4 carbon atoms, specifically, hydrogen, a methyl group, or an ethyl group.
[0106] When the unit of Chemical Formula 2 is contained, it may be contained in the acrylic copolymer in a ratio of about 0.001 to 5 parts by weight per 100 parts by weight of the alkyl (meth)acrylate unit, and at such a ratio, the desired adhesive layer can be effectively formed by irradiation with electromagnetic waves.
[0107] In another example, the acrylic copolymer may not contain the unit of Chemical 2 or may contain a relatively small amount of it, which is particularly advantageous when forming a relatively thick adhesive. That is, in order to form a thick adhesive, the application of a conventional solvent-based adhesive composition is not appropriate, and a so-called solventless or syrup-type adhesive composition may be applied. Such an adhesive composition is usually a so-called radical reaction type. When the acrylic copolymer contains a certain amount of the unit of Chemical 2 or more, when radicals are generated for curing the solventless or syrup-type adhesive composition, the overall crosslinked structure of the adhesive changes due to the radicals derived from the unit of Chemical 2, which may make it difficult to ensure the desired physical properties (e.g., low-temperature storage modulus, etc.).
[0108] Therefore, in one example, the upper limit of the ratio of the unit of Chemical 2 based on the total weight of the acrylic copolymer may be about 0.1 wt%, 0.09 wt%, 0.08 wt%, 0.07 wt%, 0.06 wt%, 0.05 wt%, 0.04 wt%, 0.03 wt%, 0.02 wt%, 0.01 wt%, 0.009 wt%, 0.008 wt%, 0.007 wt%, 0.006 wt%, 0.005 wt%, 0.004 wt%, 0.003 wt%, 0.002 wt%, or 0.001 wt%, and the lower limit may be about 0 wt%. The ratio may be less than or equal to any of the upper limits mentioned above, or may be greater than or equal to any of the lower limits mentioned above, but less than or equal to any of the upper limits mentioned above.
[0109] In another example, the upper limit of the ratio of the units of Chemical formula 2 to 100 parts by weight of the alkyl (meth)acrylate units may be about 0.2 parts by weight, 0.15 parts by weight, 0.1 parts by weight, 0.05 parts by weight, 0.01 parts by weight, 0.005 parts by weight, 0.004 parts by weight, 0.003 parts by weight, 0.002 parts by weight, 0.001 parts by weight, 0.00095 parts by weight, or 0.0009 parts by weight, and the lower limit may be about 0 parts by weight. The ratio may be less than or equal to any of the upper limits mentioned above, or may be greater than or equal to any of the lower limits mentioned above, but less than or equal to any of the upper limits mentioned above.
[0110] Meanwhile, the solventless or syrup type PSA composition refers to a PSA composition that contains a mixture of a high molecular weight component and a low molecular weight component (e.g., a mixture of a prepolymer or a polymer (including a prepolymer) and a diluent monomer) as a main component and is substantially free of a solvent or has a limited solvent content.
[0111] For example, in the solventless or syrup-type pressure-sensitive adhesive composition, the upper limit of the content of the solvent (such as a general organic solvent or aqueous solvent) based on the total weight of the pressure-sensitive adhesive composition may be about 30 wt%, 25 wt%, 20 wt%, 15 wt%, 10 wt%, 5 wt%, 1 wt%, or 0.5 wt%, and the lower limit may be about 0 wt%. In the solventless or syrup-type pressure-sensitive adhesive composition, the content of the solvent may be less than or equal to any of the above-mentioned upper limits, or may be greater than or equal to any of the above-mentioned lower limits but less than or equal to any of the above-mentioned upper limits.
[0112] The acrylic copolymer may be a copolymer having a weight average molecular weight of 1,000,000 or more. In this specification, the weight average molecular weight means a polystyrene equivalent value measured by GPC (gel permeation chromatography).
[0113] The lower limit of the weight average molecular weight of the copolymer may be about 1.1 million, 1.2 million, 1.3 million, 1.4 million, or 1.5 million, and the upper limit may be about 5 million, 4 million, 3 million, 2.5 million, 2 million, 1.9 million, 1.8 million, 1.7 million, 1.6 million, or 1.55 million. The weight average molecular weight may be less than or equal to any of the upper limits mentioned above, or greater than or equal to any of the lower limits mentioned above, or greater than or equal to any of the lower limits mentioned above but less than or equal to any of the upper limits mentioned above.
[0114] The adhesive may further include a crosslinking agent.
[0115] The type of crosslinking agent is not particularly limited, and general crosslinking agents such as isocyanate-based compounds, epoxy-based compounds, aziridine-based compounds, and metal chelate-based compounds may be used. Such types of crosslinking agents are so-called thermal crosslinking agents that embody a crosslinked structure by application of heat, and are different from the radical crosslinking agents described below. Specific examples of the isocyanate-based compounds include one or more selected from the group consisting of tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, and any of the above-mentioned polyols (e.g., trimethylolpropane). Specific examples of the epoxy-based compounds include ethylene glycol diglycidyl ether, triglycidyl ether, trimethylolpropane triglycidyl ether, and the like. Specific examples of the aziridine-based compound include, but are not limited to, one or more selected from the group consisting of N,N'-toluene-2,4-bis(1-aziridinecarboxamide), N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), triethylenemelamine, bisisopropyl 1-(2-methylaziridine) and tri-1-aziridinylphosphine oxide. Specific examples of the metal chelate-based compound include, but are not limited to, compounds in which a polyvalent metal such as aluminum, iron, zinc, tin, titanium, antimony, magnesium and / or vanadium is coordinated with acetylacetone or ethyl acetoacetate.
[0116] The crosslinking agent may be included in the adhesive in an amount of 0.01 to 10 parts by weight or 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic copolymer. The amount may be adjusted within the above range in consideration of the cohesive strength and durability of the adhesive. In one example, the ratio of the crosslinking agent may be about 0.02 parts by weight or more, about 0.03 parts by weight or more, about 0.04 parts by weight or more, about 0.05 parts by weight or more, 0.06 parts by weight or more, or about 0.07 parts by weight or more, or about 4 parts by weight or less, about 3 parts by weight or less, about 2 parts by weight or less, about 1 part by weight or less, about 0.8 parts by weight or less, about 0.6 parts by weight or less, about 0.4 parts by weight or less, about 0.2 parts by weight or less, about 0.15 parts by weight or less, about 0.1 parts by weight or less, or about 0.09 parts by weight or less.
[0117] When the content of the crosslinking agent is selected within the above content range so as to crosslink the acrylic copolymer at an appropriate level, a desired adhesive can be effectively formed.
[0118] The adhesive may contain, as the crosslinking agent, a so-called radical crosslinking agent, which is a type of crosslinking agent different from the thermal crosslinking agent. Such a crosslinking agent is particularly useful in the solventless or syrup-type adhesive composition. Such a crosslinking agent realizes a crosslinked structure by a radical reaction. In order to efficiently achieve desired properties, it may be more advantageous to apply such a radical crosslinking agent. Examples of such radical crosslinking agents include so-called polyfunctional acrylates, such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, hydroxypivalic acid, etc. acid) neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprolactone modified dicyclopentenyl di(meth)acrylate, ethylene oxide modified di(meth)acrylate, di(meth)acryloxyethyl isocyanurate, allyl cyclohexyl di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, ethylene oxide modified hexahydrophthalic acid di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, neopentyl glycol modified trimethylpropane di(meth)acrylate, adamantane di(meth)acrylate or 9,Bifunctional acrylates such as 9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, trifunctional urethane (meth)acrylate, or tris(meth)acryloxyethyl isocyanurate, diglycerides, Examples of the acrylate include, but are not limited to, tetrafunctional acrylates such as phosphorus tetra(meth)acrylate or pentaerythritol tetra(meth)acrylate, pentafunctional acrylates such as propionic acid modified dipentaerythritol penta(meth)acrylate, and hexafunctional acrylates such as dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate, or urethane(meth)acrylate (e.g., a reaction product of an isocyanate monomer and trimethylolpropane tri(meth)acrylate).
[0119] The radical crosslinking agent may be present in the pressure-sensitive adhesive layer in an appropriate ratio depending on the purpose. For example, the lower limit of the weight ratio of the radical crosslinking agent relative to 100 parts by weight of the acrylic copolymer may be about 0.001 parts by weight, 0.005 parts by weight, 0.01 parts by weight, 0.02 parts by weight, 0.03 parts by weight, 0.04 parts by weight, or 0.05 parts by weight, and the upper limit of the weight ratio of the radical crosslinking agent relative to 100 parts by weight of the acrylic copolymer may be about 10 parts by weight, 9.5 parts by weight, 9 parts by weight, 8.5 parts by weight, 8 parts by weight, 7.5 parts by weight, The ratio may be about 7 parts by weight, 6.5 parts by weight, 6 parts by weight, 5.5 parts by weight, 5 parts by weight, 4.5 parts by weight, 4 parts by weight, 3.5 parts by weight, 3 parts by weight, 2.5 parts by weight, 2 parts by weight, 1.5 parts by weight, 1 part by weight, 0.9 parts by weight, 0.8 parts by weight, 0.7 parts by weight, 0.6 parts by weight, 0.5 parts by weight, 0.4 parts by weight, 0.3 parts by weight, 0.2 parts by weight, 0.1 parts by weight, 0.09 parts by weight, 0.08 parts by weight, 0.07 parts by weight, 0.06 parts by weight, or 0.05 parts by weight. The ratio may be less than or equal to any of the upper limits mentioned above, or greater than or equal to any of the lower limits mentioned above, or greater than or equal to any of the lower limits mentioned above but less than or equal to any of the upper limits mentioned above.
[0120] In addition to the above components, the adhesive may contain appropriate additive components as necessary, and may further contain components such as a radical initiator, an ultraviolet absorber, a light stabilizer, a plasticizer and / or a crosslinking catalyst.
[0121] The pressure-sensitive adhesive of the present application may be formed by crosslinking a pressure-sensitive adhesive composition containing the above-mentioned components. The method of forming the pressure-sensitive adhesive layer by crosslinking is not particularly limited, and the pressure-sensitive adhesive may be formed by applying an appropriate crosslinking method in consideration of the type of adhesive polymer and / or crosslinking agent applied. For example, if the polymer and / or crosslinking agent is of a type that is crosslinked by application of heat, a crosslinked product may be formed by applying appropriate heat, if the polymer and / or crosslinking agent is of a type that is crosslinked by irradiation of electromagnetic waves, a crosslinked product may be formed by irradiation of appropriate electromagnetic waves, or other crosslinking methods may also be applied.
[0122] For example, the pressure sensitive adhesive may be a cured or crosslinked product of the above-mentioned solventless or syrup type pressure sensitive adhesive composition.
[0123] Such adhesives can exhibit the elastic modulus characteristics described above.
[0124] The pressure-sensitive adhesive of the present application may be in a layer form. In this case, the thickness of the pressure-sensitive adhesive layer is not particularly limited, and may have a normal thickness of a pressure-sensitive adhesive layer in consideration of the intended use.
[0125] The adhesive of the present application can meet the required properties described above, especially when formed into a thick film.
[0126] For example, the lower limit of the thickness of the adhesive may be about 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, or 100 μm, and the upper limit may be about 1000 μm, 900 μm, 800 μm, 700 μm, 600 μm, 500 μm, 400 μm, 300 μm, 200 μm, 150 μm, or 100 μm. The thickness may be less than or equal to any of the upper limits mentioned above, or greater than or equal to any of the lower limits mentioned above, or greater than or equal to any of the lower limits mentioned above but less than or equal to any of the upper limits mentioned above.
[0127] The present application further relates to a pressure-sensitive adhesive film or optical laminate comprising a base film and a pressure-sensitive adhesive formed on one or both sides of the base film. In the case of an optical laminate, the base film may be an optical film. The pressure-sensitive adhesive may be included in a layer form.
[0128] The pressure-sensitive adhesive of the present application may be formed on one or both sides of the base film to form a pressure-sensitive adhesive film, or may be formed on one or both sides of the base film, which is an optical film, to form an optical laminate.
[0129] The type of the base film is not particularly limited. As the base film, a base film that can be generally used for forming a pressure-sensitive adhesive film may be used.
[0130] For example, the substrate film may include, but is not limited to, a PET (poly(ethylene terephthalate)) film, a PTFE (poly(tetrafluoroethylene)) film, a PP (polypropylene) film, a PE (polyethylene) film, a polyimide film, a polyamide film, a COP (cyclic olefin polymer) film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, and / or a polyimide film.
[0131] The thickness of the base film is not particularly limited, and may be any appropriate thickness within a range suitable for the purpose.
[0132] When an optical film is used as the substrate film, the type of the optical film is not particularly limited. In one example, the optical film may be a polarizing film, a polarizing plate, or a retardation film. In this case, the optical film may have a thickness in an appropriate range depending on the purpose.
[0133] The pressure-sensitive adhesive film or optical laminate may further include a release film or a protective film for protecting the pressure-sensitive adhesive layer before use, as necessary.
[0134] The present application further relates to a flexible device comprising the adhesive, adhesive film or optical laminate. The adhesive may be included in a layer. There is no particular limitation on the application form of the adhesive, adhesive film or optical laminate in the device. For example, the adhesive may be used in the device as a so-called OCA (Optically Clear Adhesive) or OCR (Optically Clear Resin), and therefore the application form of the adhesive, adhesive film or optical laminate may be the same as the application form of a normal OCA or OCR.
[0135] In this case, in one example, the flexible device may include a display panel and the adhesive, adhesive film, or optical laminate present on one or both sides of the display panel, where the display panel may be configured to be folded or rolled about one or more folding or rolling axes.
[0136] Other elements constituting the flexible device as described above are not particularly limited, and known components of a flexible device may be adopted without any limitations. Effect of the Invention
[0137] The present application may provide a highly reliable adhesive that is applied to flexible devices, effectively handles repeated deformation and recovery, does not cause defects (e.g., observation of deformation marks, etc.) before and after deformation, has excellent cuttability, workability and recovery, and does not induce lifting, peeling and / or air bubble generation, etc. The present application may further provide an adhesive film or optical film containing the adhesive, and a flexible device such as a foldable device or a rollable device. [Brief description of the drawings]
[0138] [Figure 1] FIG. 13 is a diagram showing a process in which a folding test is performed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0139] The present application will be described in detail with reference to the following examples, but the scope of the present application is not limited to the following examples.
[0140] 1. Temperature sweep method for measuring storage modulus The storage modulus was evaluated using ARES G2 (Advanced Rheometric Expansion System G2) (TA). A test specimen was prepared by cutting an adhesive layer having a thickness of about 0.8 mm into a circle having a diameter of about 8 mm. The adhesive layer was prepared by stacking adhesive layers having a thickness of about 25 μm to a thickness of about 0.8 mm. The storage modulus of the test specimen at the measurement temperature was evaluated using a parallel plate fixture having a diameter of about 8 mm. The evaluation conditions were a frequency of 1 Hz and a strain of 0.5%. The temperature-specific storage modulus was confirmed while increasing the measurement temperature from -60°C to 90°C at a heating rate of about 10°C / min.
[0141] 2. Storage modulus measurement method (Frequency sweep) The storage modulus was evaluated using ARES G2 (Advanced Rheometric Expansion System G2) (TA). A test specimen was manufactured by cutting an adhesive layer having a thickness of about 0.8 mm into a circle having a diameter of about 8 mm. The adhesive layer was manufactured by stacking adhesive layers having a thickness of about 25 μm to the thickness of about 0.8 mm. The storage modulus of the test specimen was evaluated using a parallel plate fixture having a diameter of about 8 mm. The evaluation conditions during the evaluation were a frequency range of 0.1 rad / sec to 100 rad / sec and a strain of 5.0%. The measurement temperature was 30°C.
[0142] 3. Evaluation of melting point and glass transition temperature The melting point and glass transition temperature were measured by a measurement method using a DSC (Differential Scanning Calorimeter) instrument. The DSC2500 instrument (TA Instruments) was used as the equipment. Approximately 10 mg of the sample (copolymer) was filled into a dedicated pan, and the endothermic and exothermic amounts were confirmed according to the temperature under a N2 atmosphere with a heating rate of 10 °C / min and a cooling rate of -10 °C / min, and the melting point and glass transition temperature were measured.
[0143] The measurement temperature range was -120 °C to 200 °C. The conditions were as follows: First, it was cooled from room temperature (about 30 °C) to -120 °C at a rate of about -10 °C / min, and then heated to 200 °C again at a heating rate of 10 °C / min (primary heating). Thereafter, it was cooled to -120 °C again at a rate of about -10 °C / min, and then heated to 200 °C again at a heating rate of 10 °C / min (secondary heating).
[0144] The melting point and glass transition temperature were evaluated during the secondary heating.
[0145] 4. Evaluation of weight-average molecular weight The weight-average molecular weight (Mw) of the copolymer was measured using GPC (Gel Permeation Chromatograph), and the measurement conditions were as follows. When preparing the calibration curve during the measurement of the weight-average molecular weight, the measurement results were converted using standard polystyrene (manufactured by Aglient system).
[0146] <GPC measurement conditions> Measuring instrument: Aglient GPC (Aglient 1200 series, U.S.) Columns: Two PL Mixed B columns connected in series Column temperature: 40 °C Eluent: THF (Tetrahydrofuran) Flow rate: 1.0 μL / min Concentration: ~1 mg / mL (100 μl injection)
[0147] 5. Folding test The folding test was performed on a sample prepared by sequentially laminating a PI film (polyimide film, approximately 50 μm thick) with hard coating treatment on both sides, an adhesive layer produced in the examples, and an ITO (Indium Tin Oxide) film (ITO layer / PET film laminate structure) approximately 50 μm thick, and cutting the laminate into a rectangle approximately 2.54 cm wide and 20 cm long.
[0148] As shown in FIG. 1, the test piece was repeatedly folded by sandwiching it between parallel plates spaced 5 mm apart at -20°C, and after collecting the sample, the sample was visually inspected for defects such as the occurrence of bubbles, lifting / peeling, and cracks in the hard coat layer.
[0149] The evaluation criteria are as follows:
[0150] <Evaluation criteria> ○: No air bubbles, lifting / peeling, or cracks in the hard coat layer occurred up to 100,000 foldings △: No air bubbles, lifting / peeling, or cracks in the hard coat layer after 50,000 folding cycles ×: After 50,000 folding cycles, one or more of the following occurred: air bubbles, lifting / peeling, and cracks in the hard coat layer.
[0151] 6. Reliability Evaluation The reliability evaluation was performed on a sample in which a soda lime glass sheet of approximately 1.1 mm thickness (H Glass Co., Ltd., 80 mm x 140 mm) and a soda lime glass sheet of approximately 0.55 mm thickness (H Glass Co., Ltd., 80 mm x 140 mm) were laminated on both sides of the adhesive layer.
[0152] The adhesive to be evaluated was cut to a size of about 70 mm x 130 mm and applied. The sample was placed in a reliability chamber at -40°C and held for 500 hours, after which the sample was recovered and observed for the generation of bubbles and changes in optical properties.
[0153] The evaluation criteria are as follows:
[0154] <Evaluation criteria> ○: No bubbles are generated, the haze change is 0.5% or less, and the change in the b* value of the CIE color coordinate is 1 or less ×: One or more of the following occurred: air bubbles, haze change rate exceeding 0.5%, and change in b* value of CIE color coordinate exceeding 1.
[0155] Production Example 1. Production of Copolymer (A) 2-Ethylhexyl acrylate (2-EHA), lauryl acrylate (LA) and 4-hydroxybutyl acrylate (HBA) were added in a weight ratio of 4:4:2 (2-EHA:LA:HBA) to a 50 mL vial (total amount: approximately 40 g) and purged with nitrogen (N2).
[0156] A photoradical initiator (Irgacure 184) was further added at a concentration of about 500 ppm, and the mixture was irradiated with light at a UVA standard of about 0.8 J / cm2 from a metal halide lamp for 20 seconds to produce copolymer (A). The copolymer (A) is in the form of a partially polymerized prepolymer, and has a weight average molecular weight of about 1.5 million.
[0157] Production Examples 2 to 9. Production of Copolymers A partially polymerized prepolymer type copolymer was prepared in the same manner as in Preparation Example 1, except that the weight ratio of the applied monomers was as shown in the following Table 1. In the following Table 1, the numerical value for each monomer means the weight ratio.
[0158] [Table 1]
[0159] The melting point and glass transition temperature measured for each copolymer of the above Production Examples are shown in the following Table 2. In the cases where the glass transition temperature or melting point was not observed in the following Table 2, the corresponding values were not recorded.
[0160] [Table 2]
[0161] Example 1. About 0.05 parts by weight of 1,6-hexanediol diacrylate was added as a curing agent to 100 parts by weight of the copolymer (prepolymer) (A) of Preparation Example 1, and about 3 parts by weight of a photoradical initiator (Irgacure 651) was added to 100 parts by weight of the copolymer (prepolymer) (A) and mixed to prepare an adhesive composition. The adhesive composition was applied onto the release surface of a release PET film, and irradiated with black light for about 3 minutes using a UV exposure curing device to form an adhesive layer with a thickness of about 100 μm (light amount: 0.8 J / cm based on UV A). 2 ).
[0162] Example 2. An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (B) of Production Example 2 was used.
[0163] Example 3. An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (C) of Production Example 3 was used.
[0164] Comparative Example 1 An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (D) of Production Example 4 was used.
[0165] Comparative Example 2 An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (E) of Production Example 5 was used.
[0166] Comparative Example 3. An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (F) of Production Example 6 was used.
[0167] Comparative Example 4. An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (G) of Production Example 7 was used.
[0168] Comparative Example 5. An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (H) of Production Example 8 was used.
[0169] Comparative Example 6. An adhesive layer was formed in the same manner as in Example 1, except that the copolymer (prepolymer) (I) of Production Example 9 was used.
[0170] The storage modulus, folding test results, and reliability test results evaluated for the pressure-sensitive adhesive layers of the Examples and Comparative Examples are summarized in Table 3 below.
[0171] [Table 3]
Claims
1. Contains an adhesive polymer, The storage modulus at −20° C. is 100,000 Pa or less, A pressure-sensitive adhesive, wherein the absolute value of the rate of change in storage modulus ΔG1′ according to the following formula 1 is 1,700 or less. [Formula 1] △G1'=(G' 25 -G' -20 ) / 45 In the above formula 1, G' 25 is the storage modulus of the pressure sensitive adhesive at 25° C., and G′ -20 is the storage modulus of the pressure sensitive adhesive at -20°C.
2. The pressure-sensitive adhesive according to claim 1, wherein the storage modulus at -20°C is 70,000 Pa or more.
3. The pressure-sensitive adhesive according to claim 1 , wherein the storage modulus at 25° C. is 10,000 Pa or more.
4. The pressure-sensitive adhesive according to claim 1, wherein the absolute value of the rate of change in storage modulus ΔG2′ according to the following formula 2 is 1,100 or less. [Formula 2] △G2'=(G' 60 -G' -20 ) / 80 In the above formula 2, G' 60 is the storage modulus of the pressure sensitive adhesive at 60° C., and G′ -20 is the storage modulus of the pressure sensitive adhesive at -20°C.
5. The pressure-sensitive adhesive according to claim 1, having a storage modulus at 60°C of 10,000 Pa or more.
6. The pressure-sensitive adhesive according to claim 1, wherein the absolute value of the rate of change in storage modulus ΔG3′ according to the following formula 3 is 600 or less. [Formula 3] △G3'=(G' 60 -G' 25 ) / 35 In the above formula 3, G' 60 is the storage modulus of the pressure sensitive adhesive at 60° C., and G′ 25 is the storage modulus of the pressure sensitive adhesive at 25°C.
7. TM in the following formula 4 is 400 μm MPa -1 The pressure-sensitive adhesive according to claim 1 . [Formula 4] TM=D / G' -20 In the formula 4, D is the thickness of the adhesive, and G' -20 is the storage modulus of the pressure sensitive adhesive at -20°C.
8. The adhesive according to claim 1 , wherein the adhesive polymer is an acrylic copolymer that simultaneously exhibits a glass transition temperature and a melting temperature.
9. The pressure-sensitive adhesive according to claim 8, wherein the acrylic copolymer has a glass transition temperature of -30°C or lower and a melting temperature of -10°C or lower.
10. The pressure-sensitive adhesive according to claim 8, wherein the difference between the melting temperature and the glass transition temperature (Tm-Tg) of the acrylic copolymer is 15°C or more.
11. The pressure-sensitive adhesive according to claim 8, wherein the acrylic copolymer comprises an alkyl (meth)acrylate unit, a unit of the following formula 1, and a polar functional group-containing unit. 【Chemistry 1】 In the above formula 1, R 1 represents hydrogen or an alkyl group; R 2 represents an alkyl group having 11 to 13 carbon atoms.
12. The pressure-sensitive adhesive according to claim 11, wherein the alkyl (meth)acrylate unit has a linear or branched alkyl group having 1 to 10 carbon atoms, and the polar functional group-containing unit is a hydroxy group-containing monomer unit.
13. The pressure-sensitive adhesive according to claim 11, wherein the acrylic copolymer contains 10 to 60% by weight of the alkyl (meth)acrylate unit.
14. The pressure-sensitive adhesive according to claim 11, wherein the acrylic copolymer contains 80 to 600 parts by weight of the unit of Chemical 1 per 100 parts by weight of the alkyl (meth)acrylate unit.
15. The pressure-sensitive adhesive according to claim 11, wherein the acrylic copolymer contains 10 to 200 parts by weight of a polar functional group-containing unit per 100 parts by weight of the alkyl (meth)acrylate unit.
16. The adhesive according to claim 1, wherein the adhesive polymer does not contain a monomer unit of the following formula 2, or contains the monomer unit of the following formula 2 in an amount of 0.1 wt% or less based on the total weight of the adhesive polymer. 【Chemistry 2】 In the above formula 2, R 1 represents hydrogen or an alkyl group; R 3 is an aromatic ketone group or a (meth)acryloyl group.
17. The adhesive of claim 1 , further comprising a radical crosslinking agent.
18. The pressure-sensitive adhesive according to claim 1 , which is a cured product of a solventless or syrup-type pressure-sensitive adhesive composition.
19. An adhesive film comprising a base film and the adhesive according to any one of claims 1 to 18 formed on one or both sides of the base film.
20. a display panel configured to be foldable or rollable about one or more folding or rolling axes; A flexible device comprising the adhesive of any one of claims 1 to 18 present on one or both sides of the display panel.
Citation Information
Patent Citations
Adhesive agent layer for flexible image display device, laminate body for flexible image display device, and flexible image display device
JP2019218513A
Adhesive film and display member including the same
US20160177147A1
Adhesive layer
WO2021118248A1
